Penguatan Layanan Keiwirausahaan Berbasis Masyarakat di PKBM Rumah Pintar Melalui Aplikasi ROOMPI - auliya, yudha alif; Fadah, Isti; Baihaqi, Yustri (LPPM Universitas PGRI Argopuro Jember, 2025)
Karangharjo Village, located in the Silo District of Jember Regency, exhibits a low level of community education and an economic resilience rating that falls below the national average. During the inaugural year, the collaborative service initiative with PKBM Rumah Pintar concentrated on enhancing application-oriented educational services through ROOMPI. Preliminary assessments indicated an immediate necessity to enhance community entrepreneurial capabilities, especially in financial literacy, digital marketing, and technology application. Consequently, in the advanced phase, the application-oriented entrepreneurship service ROOMPI-HUB was created as a digital platform to enhance micro-business competencies. The employed approaches include of needs assessment, thematic training, mentoring, and the creation of prototype-based application functionalities. The recently introduced feature, the Digital Business Hub, enables students and the public to access interactive modules, discussion forums, and entrepreneurship training services. The training materials encompass financial literacy, micro-business management, product photography, digital branding, and marketing methods through marketplaces. The activity's results indicate a substantial enhancement in competence, as evidenced by pre-tests and post-tests of 20 participants, reflecting an average increase of 62.5%. Specifically, comprehension of photography rose by 63.2%, product downstreaming by 58.1%, digital branding by 68.9%, and digital marketing techniques by 63.8%. The attendance percentage attained 95%, with 90% of participants evaluating the program as pertinent to their enterprises, and 80% indicating their preparedness to implement sustainable digital initiatives. This program not only promoted technological innovation through ROOMPI-HUB but also effectively enhanced the entrepreneurial literacy of the Karangharjo community. The integration of technology with practical training has demonstrated the ability to enhance the competitiveness of micro-enterprises within the SME sector. To maintain the sustainability of this digital ecosystem, long-term support is essential for the continued development of applications and user capacity in accordance with local needs.